Reading development and teaching - Stuart, Morag; Stainthorp, Rhona (London : SAGE Publications Ltd, 2016)
This textbook will prove invaluable to teacher educators, teachers, educational psychologists, and any professional who is involved with teaching children to read. It provides a detailed examination of the processes that are involved in achieving fluent word reading skills and ability to comprehend written texts. Understanding these processes and their development empowers teachers to select appropriate, evidence-based teaching strategies and thus teach children more effectively. The book is in four parts: Part 1 provides the reader with a Tutorial Review covering essential knowledge about language, and presenting the two dimensions of the Simple View of Reading. Part 2 concentrates on the word reading dimension, with chapters on processes in skilled word reading, the development of these processes, and practical advice on research validated teaching methods to develop childrens word reading skills. Part 3 turns to the language comprehension dimension, with chapters on the comprehension of oral and written language, and on teaching reading comprehension. Part 4 introduces the reader to assessment practices and methods of identifying children with difficulties in either or both dimensions of the Simple View, and considers children with word reading difficulties and children with specific comprehension difficulties, describing effective evidence-based interventions for each type of difficulty.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Reading; Reading comprehension